2020
DOI: 10.3390/genes11040432
|View full text |Cite
|
Sign up to set email alerts
|

The Peptidoglycan Biosynthesis Gene murC in Frankia: Actinorhizal vs. Plant Type

Abstract: Nitrogen-fixing Actinobacteria of the genus Frankia can be subdivided into four phylogenetically distinct clades; members of clusters one to three engage in nitrogen-fixing root nodule symbioses with actinorhizal plants. Mur enzymes are responsible for the biosynthesis of the peptidoglycan layer of bacteria. The four Mur ligases, MurC, MurD, MurE, and MurF, catalyse the addition of a short polypeptide to UDP-N-acetylmuramic acid. Frankia strains of cluster-2 and cluster-3 contain two copies of murC, while the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
(81 reference statements)
0
2
0
Order By: Relevance
“…Another important distinctive gene is murC , related to peptidoglycan biosynthesis. Different copies in the genomes of the four different clusters were found ( Berckx et al, 2020 ). Two copies, mur C1 and mur C2, are present in clusters 2 and 3, which differ in their orientation with the presence of an open reading frame (ORF) encoding a nitroreductase family deazaflavin-dependent oxidoreductase in cluster 3.…”
Section: Resultsmentioning
confidence: 99%
“…Another important distinctive gene is murC , related to peptidoglycan biosynthesis. Different copies in the genomes of the four different clusters were found ( Berckx et al, 2020 ). Two copies, mur C1 and mur C2, are present in clusters 2 and 3, which differ in their orientation with the presence of an open reading frame (ORF) encoding a nitroreductase family deazaflavin-dependent oxidoreductase in cluster 3.…”
Section: Resultsmentioning
confidence: 99%
“…BMG5.1) cluster-2 forms the earliest branching and deep-rooted evolutionary group that nodulates the actinorhizal plants from Cucurbitales, Datiscaceae, Coriariaceae, Rosaceae, and Rhamnaceae [4,36,68,78,79]. In contrast, a study on Mur ligase genes (MurC, MurD, MurE, and MurF) that are involved in catalyzing the biosynthesis of bacterial peptidoglycan layer, have revealed sharing of two copies of murC among cluster-2 and cluster-3, while cluster-1 and cluster-4 shared one copy [80]. However, a higher similarity with that of Actinobacteria proteins indicated that murC might have got acquired in all Frankia strains either from a horizontal gene movement or a convergent evolution.…”
Section: Molecular Phylogeny Of Actinorhizal Microsymbiontsmentioning
confidence: 99%